The Effect Of Service Quality And Work Discipline Of Officers On Public Awareness And Compliance In Conducting Motor Vehicle Testing At The Ujung Menteng Motor Vehicle Testing Management Unit Of DKI Jakarta Province - Dony Erlan Prasetiyo; Femmy Sofie Schouten; Prasadja Ricardianto (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2025)
In the context of periodic motor vehicle testing, this study investigated the relationship between service quality and officer work discipline on public awareness and compliance. This study is based on the fact that the level of public compliance is still low and there is a difference between operational practices and operational standards at the Motor Vehicle Testing Management Unit (UPPKB) Ujung Menteng, DKI Jakarta. This study uses a quantitative and survey approach. Structural Equation Modeling (SEM) with Partial Least Squares (PLS)-based variants was used to analyze data collected from questionnaires given to 170 service users. The results showed that service quality and work discipline significantly affected public awareness, but neither directly affected compliance. There is evidence that public awareness is a fully mediating factor, or full mediation, that significantly influences compliance and is an indirect pathway to work discipline and quality of service. These results show that service strategies should focus on improving technical procedures and education to raise awareness as the key to improving sustainable compliance